2013
DOI: 10.1371/journal.pone.0081826
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Machine Perfusion Reduces Delayed Graft Function and Improves One-Year Graft Survival of Kidneys from Expanded Criteria Donors: A Meta-Analysis

Abstract: BackgroundExpanded criteria donors (ECDs) are currently accepted as potential sources to increase the donor pool and to provide more chances of kidney transplantation for elderly recipients who would not survive long waiting periods. Hypothermic machine perfusion (HMP) is designed to mitigate the deleterious effects of simple cold storage (CS) on the quality of preserved organs, particularly when the donor is in a marginal status.MethodsWe compared the transplant outcomes in patients receiving ECD kidneys with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 29 publications
(44 reference statements)
1
59
2
1
Order By: Relevance
“…Despite the fact that these studies grouped together different categories of donors (standard donors, non‐heart beating donors, expanded criteria donors, etc. ), smaller or retrospective studies, that have specifically examined only one donor type, showed similar results , although no differences in 1‐year graft survival rate were identified. On the basis of these results, several authors asserted that the systematic use of HMP for DCD and ECDs graft reconditioning can be considered cost‐effective in terms of savings for DGF and PNF cases .…”
Section: Discussionmentioning
confidence: 59%
“…Despite the fact that these studies grouped together different categories of donors (standard donors, non‐heart beating donors, expanded criteria donors, etc. ), smaller or retrospective studies, that have specifically examined only one donor type, showed similar results , although no differences in 1‐year graft survival rate were identified. On the basis of these results, several authors asserted that the systematic use of HMP for DCD and ECDs graft reconditioning can be considered cost‐effective in terms of savings for DGF and PNF cases .…”
Section: Discussionmentioning
confidence: 59%
“…43 A US registry analysis demonstrated that machine perfusion reduces the risk of DGF and 1-year graft failure by approximately 50% versus cold storage 42 ; however, there was no significant difference in the magnitude of the treatment effect on DGF with SCDs versus ECDs. 42 A meta-analysis demonstrated similar results, 44 whereas in a separate study, graft survival remained significantly higher in the machine perfusion group at year 3. 45 Kwiatkowski et al 46 reported a significant improvement in both graft survival and renal function at 5 years.…”
Section: Early Ischemic Injury and Dgf In Kidney Transplantationmentioning
confidence: 82%
“…When comparing standard static cold storage in kidneys vs. use of HMP for preservation, studies have shown the HMP group kidneys to have a lower incidence of delayed graft function, although there remains controversy regarding long-term graft survival and patient survival rates [39][40][41][42][43][44]. When comparing standard static cold storage in kidneys vs. use of HMP for preservation, studies have shown the HMP group kidneys to have a lower incidence of delayed graft function, although there remains controversy regarding long-term graft survival and patient survival rates [39][40][41][42][43][44].…”
Section: Machine Perfusionmentioning
confidence: 99%